Hubungan Kehamilan Ganda dengan Kejadian Preeklampsia - Budi Rahayu (Prodi D III Kebidanan Fakultas Ilmu Kesehatan Universitas Ibrahimy, 2023)
Complications in pregnancy include the onset of hypertension accompanied by protein in the urine that appears when the pregnancy reaches 20 weeks is called preeclampsia. Appropriate management and early detection is needed in cases of preeclampsia, if treatment is late, the condition will deteriorate very quickly which can lead to eclampsia. Eclampsia eventually causes the condition of the fetus and mother to worsen and increases morbidity and mortality. There are many risk factors for preeclampsia including parity, age of the mother during pregnancy, multiple pregnancies, and previous history. The purpose of this study was to identify the relationship between multiple pregnancies and cases of preeclampsia. This study used the case control method and the retrospective time approach, taking samples with purposive sampling, and processing data using the Fisher's test with the strength of the relationship using the odds ratio (OR). The results of this study were p value 0.03 <0.05, with an OR value of 1.607 meaning that pregnant women with multiple pregnancies 1.6 times will experience preeclampsia in pregnancy.